Jihadists and Refugees at the Theatre: Global Conflicts in Classroom Practices in Sweden - Karin K. Flensner; Göran Larsson; Roger Säljö (MDPI AG, 2019)
In democratic societies schools have an obligation to address complex societal issues such as ethnic/religious tensions and social conflicts. The article reports an exploratory study of how theatre plays were used in upper-secondary schools to generate pedagogically relevant platforms for addressing the current Middle East conflicts and their impact on European societies in the context of religious education and civics. The schools are situated in areas with substantive migrant populations of mixed backgrounds, and this has implications for how these issues are understood as a lived experience. In the same classrooms, there were students who had refugee backgrounds, who represented different interpretations of Islam, and religion more generally, and whose families were victims of terrorism. There were also students with strong nationalist views. The study is ethnographic documenting theatre visits and classroom activities in relation to two plays about the Middle East situation. The results show that plays may open up new opportunities for addressing these issues, but that they may also be perceived as normative and generate opposition. An interesting observation is that a play may generate space for students to tell their refugee story in class, which personalized the experience of what it means to be a refugee.